Development, implementation, and evaluation of an interactive smoking cessation intervention workshop for dental students (SCIDs) - Yahya, Nurul Asyikin; Abllah, Zurainie; Rani, Haslina; Liew, Amy Liew Kia Cheen; Che Musa, Muhd Firdaus (2018)
Shifting from traditional classroom teaching to interactive-learning methods represents an essential component of current thinking in dental education. Considering this trend, an interactive workshop was conducted as part of the scheduled smoking-cessation activity in the dental curriculum. The objective of this study was to develop, implement, and evaluate an Interactive Smoking Cessation Intervention Workshop for Dental Students (SCIDs). A one-day workshop on Smoking Cessation Intervention for Dental Students (SCIDs) module was developed, validated by experts and conducted on fifty-three Year 4 dental students in UKM. Dental students’ knowledge on smoking cessation was assessed pre-workshop via Kahoot online game. Eleven questions were asked with 20 seconds time allotted for each question. Overall performance showed the total correct answers were 70.45%; total incorrect answers were 29.55% with an average score of 6164.04 points in Kahoot. A post-workshop evaluation was also conducted. Most students agreed that the workshop content was relevant to them (95%); lived up to their expectations (95%); stimulated their learning (90%) and the workshop activities gave them sufficient practice and feedbacks (90%). SCIDs workshop could provide students with the support needed to acquire skills in conducting smoking cessation intervention to their patients.